2015
DOI: 10.1253/circj.cj-14-1079
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation in Peripheral Endothelial Function After Continuous Flow Left Ventricular Assist Device Therapy Is Associated With Cardiovascular Adverse Events

Abstract: Background:Patients with heart failure (HF) have abnormal endothelial function. Although use of a continuous flow left ventricular assist device (CF-LVAD) results in significant hemodynamic improvement, the effects on systemic endothelial function are unclear. Methods and Results:Eighteen HF patients with CF-LVAD implantation were included in this prospective observational study. We measured reactive hyperemia index (RHI) before and after CF-LVAD implantation to evaluate sequential changes in endothelial funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 49 publications
0
30
0
1
Order By: Relevance
“…In addition, these chronic HFrEF patients would be expected to have endothelial dysfunction involving the coronary arteries or systemic vasculature, conditions that would further contribute to the patients’ morbidity, exercise intolerance, and mortality. 124127,155,156…”
Section: Dream-hf Trial: Key Phase III Trial Design Aspects For Evalumentioning
confidence: 99%
“…In addition, these chronic HFrEF patients would be expected to have endothelial dysfunction involving the coronary arteries or systemic vasculature, conditions that would further contribute to the patients’ morbidity, exercise intolerance, and mortality. 124127,155,156…”
Section: Dream-hf Trial: Key Phase III Trial Design Aspects For Evalumentioning
confidence: 99%
“…WSS is a very important hemodynamic factor believed to have critical effects on regulating the structure and function of endotheliocytes. For instance, Hasin et al reported that the endothelial function showed a significant and persistent decline under excessive WSS condition [ 27 ]. Uzarski et al reported that the excessive shear stress magnitude could elicit phenotypic changes relevant to their critical roles in thrombosis, hemostasis, and inflammation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Templeton et al reported that vascular compliance was impaired by the use of LVAD support [ 30 ]. In addition, Hasin et al found that the peripheral endothelial function was attenuated after LVAD therapy [ 31 ]. From the hemodynamic view point, the changes in hemodynamic states, especially in the swirling flow characteristic, play an important role in these complications.…”
Section: Discussionmentioning
confidence: 99%